Two-step electrochemical synthesis of "ant-nest" like Co-O, pyrrolic N co-modified graphite felt for high-efficient H2O2 production. (1st December 2022) - Fu, Dengyu; Zhu, Yanji; Chen, Lei; Sun, Yue; Zhang, Meng; Wang, Huaiyuan
Abstract: Heteroatom modified catalyst applying for the two-electron oxygen reduction reaction has the potential application for efficient on-site production of H2 O2 . At present, state of the art catalyst synthesis is often energy-intensive and tends to destroy the original structure of heteroatoms. Based on the above considerations, Co-O, pyrrolic N structures co-modified graphite felt catalyst (Co-PDA-GF) is successfully synthesized by a simple two-step electrochemical method. Interestingly, the introduction of Co 2+ during the dopamine (DA) polymerization process changes the surface morphology of GF from a "thin-film" like to an "ant-nest" like. The cumulative H2 O2 concentration achieves 421 mg L −1 in 6 h test time, which is 16 times higher than that of R-GF, and the Methylene blue (MB) in-situ removal rate reaches 97.2% within 3 h. The enhanced H2 O2 yield of Co-PDA-GF catalyst is attributed to the increased oxygen-containing functional groups (-COOH, -C-O-C) and defect structures, and most importantly, Co-O and pyrrolic N synergistic modulation effects on local electronic modulation. This work provides new insights on DA polymerization morphology control and designing of high-efficient 2e − ORR catalyst with a low-energy method. Highlights: Two-step electrochemical synthesis of Co-PDA deposited graphite felt catalyst. The Co 2+ introduction changes the surface PDA morphology of GF from "thin-film" like to "ant-nest" like. Excellent electrosynthesis H2 O2 performance with a cumulative concentration of 421 mg L −1 . Electrochemical method enables the oriented synthesis of pyrrolic N configurations. Graphical abstract: The in-situ modification of graphite felt by a rapid two-step electroporation method successfully introduced "ant-nest" like Co 2+ and pyrrolic N structures at the surface, realizing high-efficient H2 O2 production. Image 1